Use of minute duckweed (Lemna perpusilla) for supplemental feed in catfish (Clarias sp.) culture: determination of the optimal proportion using powersim simulation - Chrismadha Tjandra (EDP Sciences, 2021)
Catfish farming is very profitable because the fish is easy to rear and can be harvested quickly. However, the cost of feed as the most significant component in production costs is currently getting higher. The availability and utilization of alternative feed is an urgent solution in creating sustainable catfish farming. This research was carried out during December 2020 – January 2021 in the Research Center for Limnology, Cibinong, Indonesia, which aims to determine the optimal proportion of minute duckweed (Lemna perpusilla) biomass added as feed supplemental to obtain an optimum growth of catfish fingerlings (Clarias sp.). Catfish were reared for 63 days in nine aquariums with a density of 25 fish per aquarium. The commercial pellet given in the control aquarium was 100% pellet portion (5% of the total fish weight), while in the treatment aquariums were 60% and 40% of the total fish weight. As compensation, fresh duckweed (L. perpusilla) was provided ad libitum. Fish were sampled twice to measure their weight and body length. This study showed that the proportion of duckweed as much as 40% as a supplement for commercial pellets could produce optimal catfish growth.